2011
DOI: 10.3390/ijms12063770
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Soil Properties and Bacterial Communities between the Rhizosphere and Bulk Soil and among Different Production Areas of the Medicinal Plant Fritillaria thunbergii

Abstract: To explore rhizosphere effects, geographical differences and their effects on the bacterial community associated with the geoherb Fritillaria thunbergii, some physicochemical properties of soil samples (3 sampling sites × 2 habitats (rhizosphere and bulk soil)) were measured and the soil bacterial community detected by PCR-denaturing gradient gel electrophoresis (DGGE). Among the three regions, soil pH varied between 4.48 and 7.73 indicating that F. thunbergii could grow both in acid and slightly alkaline soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 16 publications
3
34
0
7
Order By: Relevance
“…The increase in the number of cells per gram of soil leads to variation in local environmental conditions, thereby for example, promoting a decrease in oxygen availability as it is rapidly consumed by the higher microbial biomass (Philippot et al, 2013). This scenario means that other local parameters can also vary, for example, the pH (commonly lower in the rhizosphere), the organic carbon content (commonly higher in the rhizosphere), and the activity of enzymes produced by microbial cells (Shi et al, 2011).…”
Section: Plant Selection For the Rhizosphere Microbial Communitiesmentioning
confidence: 99%
“…The increase in the number of cells per gram of soil leads to variation in local environmental conditions, thereby for example, promoting a decrease in oxygen availability as it is rapidly consumed by the higher microbial biomass (Philippot et al, 2013). This scenario means that other local parameters can also vary, for example, the pH (commonly lower in the rhizosphere), the organic carbon content (commonly higher in the rhizosphere), and the activity of enzymes produced by microbial cells (Shi et al, 2011).…”
Section: Plant Selection For the Rhizosphere Microbial Communitiesmentioning
confidence: 99%
“…However, the same secondary metabolites (e.g., several groups of alkaloids and cardiac glycosides) in other plant taxa that are not closely related in a phylogenetic context are also found (Rønsted et al, 2008;Wink et al, 2010). Fourth, as the rhizosphere bacteria and the soil properties have a close relationship with the geoherbalism of F. thunbergii (Shi et al, 2011), it is intriguing to investigate how these biotic and abiotic factors shape the chemical profiles of various Fritillaria species. Second, the genes encoding the enzymes of steroidal alkaloid biosynthesis might be regulated transcriptionally, that is, they are switched on or off in a certain context.…”
Section: Phylogenymentioning
confidence: 99%
“…The scientific connotation of geoherbs quality and the relationship between the quality and efficacy of geoherbs are the emphases and difficulty in the study of geoherbs. MC is one of the commonly used TCM with significant activity against DN [13]. The prevention of MC on DN included series pharmacological effects, including its improvement on the basement membrane thickening, oxidative stress, inflammation, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Peaks (No. 2,7,13,14,16,17,18,19,20,21,22, 23 and 24) in Table 4 were identified as mudanoside B, paeoniflorin sulfonate, oxypaeoniflorin, paeoniflorin, trigalloyl glucose, tetragalloyl glucose, tetragalloyl glucose, pentagalloyl glucose, hexagalloyl glucose, galloylpaeoniflorin, benzoylpaeoniflorin, mudanoside A, paeonol, as we published before ( Figure 4C) [9]. The component analysis for MC from different regions showed in Table 5 revealed that MC from each region had its own unique intrinsic ratio of active components.…”
Section: Ms Analysis and Comparison On The Content Of Active Componenmentioning
confidence: 99%